The Sustainability of Scientific Disciplines among Higher Institute Graduates and the Role of Curricula in Achieving It": Graduates of the Higher Institute of Science and Technology – Wadi Al-Ajal: An Exploratory Study - Gaith, Souad Abubker; Ekshik, Fatima Mansour Saleh (The 1st International Conference On Basic Sciences & Its Applictionss, 2024)
The study aims to observe and identify the current state of the sustainability of academic disciplines among graduates in the labor market, and to shed light on the role of academic curricula in achieving the sustainability of these disciplines for graduates of higher institutes. The researchers employed a descriptive analytical method to conduct the study and to test its hypotheses, with the goal of reaching a precise and comprehensive scientific description of the problem. The study sample consisted of 90 male and female graduates from the Higher Institute of Science and Technology – Wadi Al-Ajal, who graduated between the Fall semester of 2014 and the Fall semester of 2022. The study yielded several findings, the most significant of which was that the current educational curricula in higher institutes have no significant impact on providing the requirements and characteristics of sustainable development in scientific disciplines. Moreover, the study found statistically significant differences in the role of academic curricula in sustaining scientific disciplines and applying them after graduation, based on variables such as gender, scientific specialization, and academic qualification.